Bovine lactoferricin B induces apoptosis of human gastric cancer cell line AGS by inhibition of autophagy at a late stage - Pan, W.-R.; Chen, P.-W.; Chen, Y.-L. S.; Hsu, H.-C.; Lin, C.-C.; Chen, W.-J. (Journal of dairy science, 2013)
Gastric cancer is one of the most common malignant cancers, with poor prognosis and high mortality rates worldwide. Therefore, development of an effective therapeutic method without side effects is an urgent need. It has been reported that cationic antimicrobial peptides can selectively bind to negatively charged prokaryotic and cancer cell membranes and exert cytotoxicity without causing severe drug resistance. In the current study, we prepared a series of peptide fragments derived from bovine lactoferrin and evaluated their anticancer potency toward the gastric cancer cell line AGS. Cell viability assay revealed that a 25-AA peptide fragment, lactoferricin B25 (LFcinB25), exhibited the most potent anticancer capability against AGS cells. Lactoferricin B25 selectively inhibited AGS cell growth in a dose-dependent manner, exhibiting a half-maximal inhibitory concentration (IC50) value of 64μM. Flow cytometry showed a notable increment of the sub-G1 populations of the cell cycle, indicating the induction of apoptosis by LFcinB25. Western blot analysis further revealed that upon LFcinB25 treatment for 2 to 6h, apoptosis-related caspases-3, 7, 8, 9, and poly(ADP-ribose) polymerase (PARP) were cleaved and activated, whereas autophagy-related LC3-II and beclin-1 were concomitantly increased. Thus, both apoptosis and autophagy are involved in the early stage of LFcinB25-induced cell death of AGS cells. However, upon treatment with LFcinB25 for 12 to 24h, LC3-II began to decrease, whereas cleaved beclin-1 increased in a time-dependent manner, suggesting that consecutive activation of caspases cleaved beclin-1 to inhibit autophagy, thus enhancing apoptosis at the final stage. These findings provide support for future application of LFcinB25 as a potential therapeutic agent for gastric cancer.